2020
DOI: 10.1007/s11575-020-00434-7
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Service Multinationals: The Degree of Internationalization and Performance

Abstract: We investigate the degree of internationalization of Chinese service multinational enterprises (MNEs) and their performance relative to global peers operating in the same industries, using the benchmarking method with the industry financial data. Our theoretical development is based upon Verbeke and Forootan (2012)’s framework, grounded in “new” internalization theory, arguing that an MNE’s financial performance is fundamentally determined by its firm-specific advantages (FSAs). Here FSAs include not only conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Between 2016 and 2020, the topics were further developed with the addition of the board’s co-working experience, the board’s influence on the director’s decision-making (Chen et al, 2017 ), home country political connection (Bai et al, 2019 ), and more recently, the degree of internationalization in service MNEs (Wei & Nguyen, 2020 ). The more recent themes have the potential for further development, with authors focusing on topics that examine boundary conditions of the internationalization and performance relationship and factors affecting the performance of service MNEs.…”
Section: Major Themes In Mir Corpusmentioning
confidence: 99%
“…Between 2016 and 2020, the topics were further developed with the addition of the board’s co-working experience, the board’s influence on the director’s decision-making (Chen et al, 2017 ), home country political connection (Bai et al, 2019 ), and more recently, the degree of internationalization in service MNEs (Wei & Nguyen, 2020 ). The more recent themes have the potential for further development, with authors focusing on topics that examine boundary conditions of the internationalization and performance relationship and factors affecting the performance of service MNEs.…”
Section: Major Themes In Mir Corpusmentioning
confidence: 99%
“…The brand internationalization degree is based on the average of the normalized value of the overseas revenue of the enterprise, in which context t is the proportion of the enterprise’s overseas revenue [ 54 ].…”
Section: Research and Data Methodologymentioning
confidence: 99%
“…The maximum ambiguity point of BE should be 77.9 (the data regarding China). Wei claimed that a brand with more than 10% overseas business is an international brand [ 54 ]. Therefore, the maximum ambiguity point of BI is 10.…”
Section: Research and Data Methodologymentioning
confidence: 99%
“…Rugman and his co-authors examined firms from emerging economies listed in FG500 and found that most are domestic by Rugman’s (1981) definition. For example, only 10% of the 500 largest Chinese manufacturing firms and 5% of the 500 largest Chinese service firms are MNEs (Rugman et al , 2016; Wei and Nguyen, 2020), whereas the rest are domestic.…”
Section: Aspects Of Firm-level Multinationality Measurementmentioning
confidence: 99%